Random forests to evaluate biotic interactions in fish distribution models. (May 2015) - Vezza, P.; Muñoz-Mas, R.; Martinez-Capel, F.; Mouton, A.
Abstract: Previous research indicated that high predictive performance in species distribution modelling can be obtained by combining both biotic and abiotic habitat variables. However, models developed for fish often only address physical habitat characteristics, thus omitting potentially important biotic factors. Therefore, we assessed the impact of biotic variables on fish habitat preferences in four selected stretches of the upper Cabriel River (E Spain). The occurrence of Squalius pyrenaicus and Luciobarbus guiraonis was related to environmental variables describing biotic interactions (inferred by relationships among fish abundances) and channel hydro-morphological characteristics. Random Forests (RF) models were trained and then validated using independent datasets. To build RF models, the conditional variable importance was used together with the model improvement ratio technique. The procedure showed effectiveness in identifying a parsimonious set of not correlated variables, which minimize noise and improve model performance in both training and validation phases. Water depth, channel width, fine substrate and water-surface gradient were selected as most important habitat variables for both fish. Results showed clear habitat overlapping between fish species and suggest that competition is not a strong factor in the study area. Highlights: We modeled fish distribution at the mesohabitat scale using Random Forests (RF). We evaluated the effect of interspecific interactions on fish habitat use. RF models are validated using an independent dataset and showed high performance. Results showed a clear habitat overlapping between fish species. Fish interspecific competition seems to be a negligible factor for habitat use.